ความรับผิดทางแพ่งในการขนส่งสินค้าอันตราย - พิมสิริ อึงขจรกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
At present. Thailand has been yearly importing increasing quantities of dangerous goods for use in industries, commerce, agriculture and in household. Transportation or carriage of such goods thus play very important role in enabling such goods reaching consumers. Even though there exist strict regulations for carriers to follow, accidents still occur during the carriage causing damage to human lives, health, properties as well as environment. According to civil and commercial code those who are liable for damages arising from the carriage of dangerous goods are those who take control of goods or vehicle or performing such goods when danger occur. As a rule the said persons are normally drivers or employee of the carriers and these people do not have enough financial resources to pay for the actual damages arising from such damage which are usually of large magnitudes. In an effort to solve the said problem, The Dangerous Substances Act B.E. 2535 and The Protect and Promotion of Environment Act B.E. 2535 were enacted but they still fail to conform with International Convention on Civil Liability for Damage caused during Carriage of Dangerous Goods by Road, Rail and Inland Navigation Vessel (CRTD) due to the fact that there has to be a limit liability on the damage borne by the carriers are required to pay for very large amount arise from damages during carriage. The carriers will have to adjust freight upwards which will in turn push up the price of such goods. The writer would therefore propose that Thailand should enact specific law to govern civil liability for the carriage of dangerous goods by incorporating principles from Convention on Civil Liability for Damage caused during Carriage of Dangerous Goods by Road, Rail and Inland Navigation Vessels (CRTD) with provisions specifying clearly the party that will be directly liable for damage arising from the carriage such as carrier and/or any other person who fail to his duty to manage the dangerous goods by law, compulsory insurance and constituting funds for payment of damages arising from carriage of dangerous goods so that the party or parties sustaining damage will receive equitable compensation while the business of carriage will not be effected too much.